Evaluation of nuclear spent fuel dry storage casks and storage facility designs - Hartnick, Megan Donna (Department of Electrical Engineering, 2017)
Koeberg Nuclear Power Station (KNPS) is the only nuclear power station in Africa and it stores its spent nuclear fuel (SNF) onsite in the spent fuel pool (SFP). Additional aged SNF assemblies are stored in dry storage casks in a facility located on the KNPS site. This minor research dissertation aims at evaluating various dry storage cask found in open literature. The dissertation provides an overview of cask types, heat transfer, radiation shielding and storage facility types. Specific criteria are required in the selection of casks and the storage facility to house the casks on site. The selection criteria for casks and the storage facility were determined and technically evaluated in this dissertation. The selected casks were evaluated in terms of SNF criticality, radiation shielding, decay heat removal and heat transfer. Other aspects also determined by calculation were the seismic stability of casks and the cask footprint. The results obtained show the relationship of the spent fuel (SF) packing density between the different casks. Different shielding materials are used in the casks and it aided the heat transfer process to take place with some casks having additional features which included cooling fins and air vents for adequate cooling of the SNF. Through these some trends could be identified which could be used in the selection or design of new storage casks. Recommendations for further study are to evaluate a greater range of casks to verify and improve upon the relationship of evaluated parameters that were shown in the technical evaluation. These casks should all have similar means of maintaining sub-criticality, shielding and heat removal in order to generate comparable results.